HELiPOD - Revolution and evolution of a helicopter-borne measurement system for multidisciplinary research in demanding environments - Pätzold, Falk; Bretschneider, Lutz; Nowak, Stefan; Brandt, Björn; Schlerf, Andreas; Asmussen, Magnus Ole; Bollmann, Sven; Bärfuss, Konrad; Harm-Altstädter, Barbara; Hecker, Peter; Wehner, Birgit; van der Wall, Berend G.; et al. (Elem Sci Anth, 2023)
The helicopter-borne measurement system HELiPOD is a platform for atmospheric and other environmental measurements to investigate local and regional phenomena. It can be operated in remote areas, as from a research vessel with a helicopter, without the need for a runway. This article presents the current design concept, technical details, and sensor package of HELiPOD, which was completely renewed for the deployment during the MOSAiC (Multidisciplinary drifting Observatory for the Study of Arctic Climate) expedition across the North Polar Ocean in 2019/2020. It was updated for the deployment in the methane campaigns METHANE-To-Go-Poland to study methane emissions from coal mines in South Poland, and METHANE-To-Go-Nordstream, a follow-up campaign to study methane emissions from the Baltic Sea after the NordStream pipeline leaks in 2022. The HELiPOD has the dimensions of 5.2 m × 2.1 m × 1.2 m and a weight of around 325 kg. It provides the possibility for flight patterns on a horizontal scale of typically 100 m–100 km and at altitudes from 10 m up to 3 km. HELiPOD employs distributed data acquisition and central data synchronization, equipped with sensors relevant to five fields of research: atmospheric dynamics, trace gases, aerosols, radiation, and surface properties. The focus of this article is the technical realization, in particular the data acquisition system for about 60 sensors, as well as concepts for energy supply and thermal management. It describes the complementary use of different measurement principles and redundant sensors for improved data quality. Operational procedures are also discussed.